Model Perjanjian Perkawinan Pasca Putusan MK No. 69/PUU-XII/2015 Perspektif Maqaṣhid al-Shari’ah Imam al-Shatibi - Muhamad Sifak; Rayno Dwi Adityo (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
This study examines the validity of the expansion of marital agreements following Constitutional Court Decision No. 69/PUU-XIII/2015, which allows such agreements to be made during the course of a marriage, unlike the previous provision under Article 29 of Law No. 1 of 1974 on marriage, which only permitted them to be made before or at the time of marriage. This type research used a normative legal method with a conceptual approach, utilizing secondary data consisting of primary legal materials, secondary, and tertiary legal materials obtained through library research and analyzed using a prescriptive approach and interpretative method. The result indicate that the expansion is legally valid as long as it fulfills the requirements of a valid agreement and does not conflict with applicable laws. From the perspective of Imam Al-Shatibi’s Maqaṣid Al-Shari’ah, this policy is consistent with the objectives of protecting property (hifz al-mal) and preservation of progeny (hifz al-nasl). Regarding the object of the agreement, its permissibility falls into the hajiyat (complementary) category, moving towards the dharuriyat (essential) in preserving those two objectives. Therefore, marital agreements can serve as a legal instrument for promoting justice, welfare, and harmony within the family.